2017
DOI: 10.1016/j.ibiod.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient degradation of organic pollutants using a microbially-synthesized nanocatalyst

Abstract: 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The Fe(II)-bearing mineral phases synthesized from these sediments removed Cr(VI) in batch reactor studies with some similarities (reactivity) to fine grain biogenic magnetite. This suggests that these bioreduced sediments are amenable to treatment of priority radionuclides [e.g., Tc(VII)], heavy metals [e.g., Cr(VI)], as tested here and Hg(II) (Wiatrowski et al, 2009), metalloids [As(V), and Se(IV)] (Scheinost and Charlet, 2008) and organics (TCE/PCE; Watts et al, 2015Watts et al, , 2016.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The Fe(II)-bearing mineral phases synthesized from these sediments removed Cr(VI) in batch reactor studies with some similarities (reactivity) to fine grain biogenic magnetite. This suggests that these bioreduced sediments are amenable to treatment of priority radionuclides [e.g., Tc(VII)], heavy metals [e.g., Cr(VI)], as tested here and Hg(II) (Wiatrowski et al, 2009), metalloids [As(V), and Se(IV)] (Scheinost and Charlet, 2008) and organics (TCE/PCE; Watts et al, 2015Watts et al, , 2016.…”
Section: Discussionmentioning
confidence: 83%
“…Fe(II) bearing nanomaterials, such as bionanomagnetite (BNM), can be used to remediate and stabilize a range of redoxactive toxic metals, e.g., Cr(VI) and Tc(VII) (Telling et al, 2009;Cutting et al, 2010;Watts et al, 2015) and, organics including nitrobenzene, azo dyes, and perchloroethylene (PCE) (Crean et al, 2012;Coker et al, 2014;Watts et al, 2016). Although bionanomagnetite can be synthesized from a range of ferric iron mineral phases (Cutting et al, 2012), existing laboratory-scale methods usually employ precursors made by using analytical grade salts of iron and strong alkali, which if used at scale, would impact on overall production costs and increase environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although this study has focused on Cr(VI) as a model contaminant, BNM can remediate a variety of other pollutants including organic contaminants such as PCE, TCE, nitrobenzene 14 and azo dyes 48 . The priority radionuclides Tc(VII) and Np(V) are also amenable to treatment via BNM-mediated reduction to reduced tetravalent phases 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Its synthesis can be regarded as a green chemistry process, operating at ambient pressures and temperatures in the absence of toxic reagents and capping agents, and it is also amenable to surface engineering for improved reactivity. For instance, BNM has been shown to abiotically reduce Pd(II) to Pd(0), producing a nanoscale heterostructure with extended reactivity against inorganic 12 , 13 and organic substrates 14 in the presence of external electron donors. Recent studies have shown that BNM synthesis is both tunable (with respect to particle size and magnetic properties) and scalable underpinning future commercial exploitation 10 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…HN-41 [ 121 , 122 ], S. piezotolerans WP3[ 123 ] and G. sulfurreducens [ 124 132 ] have been exploited to produce well-defined magnetite nanoparticles through the dissimilatory reduction of poorly crystalline Fe 3+ -oxyhydroxides. Besides, the biosynthesized magnetite nanoparticles could well support nanostructured Pd for significent improvement on functionality and applicability [ 125 , 133 ].…”
Section: Biosynthesis Of Metal Nanoparticlesmentioning
confidence: 99%